Effect of Dilution on Electrochemical Properties of Stainless Steel Clad Layer Using Submerged Arc Welding Technique - Mustafa Imhmed Elshbo; Azaldin Alhaj Kozam; Ali Benour Elhatmi; Murad A. Debeski; Muftah Aburgaiah (African Journal of Advanced Pure and Applied Sciences, 2024)
This study investigated the effect of dilution on clad layers of stainless-steel type 316L deposited via submerged arc welding technique. Metallographic and corrosion testing methods were used to examine the dilution effect. Metallographic analysis showed that the interface between the substrate and SS316L layer was more susceptible to pitting corrosion compared to the top surface layer. Corrosion tests results - including weight loss and electrochemical tests- were consistent. In electrochemical testing, the top surface of clad layers exhibited better corrosion behavior as the passivity region started at a lower potential and lasted longer, indicating superior corrosion resistance. Weight loss test results also confirmed that the top surface of the clad layer provided enhanced corrosion resistance. The corrosion seen in top clad layers due to dilution was within acceptable criteria for engineering applications in seawater.